Strength of aluminum alloys obtained on scrap base - Kovač, Risto; Siniša, Jojin (Journal of Production Engineering, 1984)
Important effects in economy of a country can be obtained by using aluminum on scrap base and its alloys, especially of they are used for developing a new alloys. This paper, deals with strehgth of Al-Cu-Mg alloys made on scrap base.